Effect of Leadership Style, Work Discipline, and Career Development on Employee Productivity of PT Yuri 8 Sejahtera - Herawati, Heny; Suldina, Farida; Lestari, Sri; Rafliansyah, Rafliansyah (Journal of Comprehensive Science, 2025)
This study aims to obtain real evidence about the influence of "leadership style, work discipline, and career development efforts on employee productivity levels at PT Yuri 8 Sejahtera". Data was obtained by distributing questionnaires to 97 employees who work in the company. Data analysis in this study involves the use of multiple regression and correlation tests. Furthermore, the model was tested for suitability through regression fit test, coefficient of determination (R²) test, F test for simultaneous, and t test for partial. As a first step, the validity and reliability of the data were tested to ensure the research instruments were consistent and accurate. From the results of analysis and hypothesis testing, it is evident that leadership style (X1), work discipline (X2), and career development (X3) have a positive and significant influence on employee work productivity (Y). Each variable shows a significance value below 0.05 and the tcount value is above the ttable. These three factors explain 96.6% of the variation in work productivity, the remaining 3.4% is influenced by other factors not included in this study. Thus, organizations need to develop integrated strategic policies in terms of leadership, discipline, and career development as part of the human resource management system. Therefore, improvement in these three aspects is highly recommended to encourage more optimal work productivity.